Vertical thermodynamic profiling of tropospheric aerosol layers in a coastal Mediterranean city: A diagnostic case-study analysis using lidar and WRF simulations - Alexandra Chudnovsky; Kevin Ohneiser; Albert Ansmann; David Avisar; Sigalit Berkovic; Fima Rotter; Dorita Rostkier-Edelstein (Atmospheric Environment, 2026)

Current Approaches for Predicting Human PK for Small Molecule Development Candidates: Findings from the IQ Human PK Prediction Working Group Survey - Carl Petersson; Xin Zhou; Joerg Berghausen; David Cebrian; Michael Davies; Kevin DeMent; Peter Eddershaw; Arian Emami Riedmaier; Alix F. Leblanc; Nenad Manveski; Punit Marathe; Panteleimon D. Mavroudis; et al. (The AAPS Journal, 2022)

Sequestration of Polystyrene Microplastics by Jellyfish Mucus - Živa Lengar; Katja Klun; Iztok Dogsa; Ana Rotter; David Stopar (Frontiers in Marine Science, 2021)
The worldwide microplastics pollution is a serious environmental and health problem that is currently not effectively mitigated. In this work we tested jellyfish mucus as a new bioflocculent material capable of sequestration of polystyrene microplastics in aqueous environments. Mucus material was collected from different jellyfish species and was used to trap fluorescently tagged polystyrene microspheres. The efficiency of removal was tested using varying concentrations of microplastics and mucus. The interaction between the microplastics and mucus was determined by viscosity measurements and confocal laser scanning microscopy. Different mucus preparation methods were also tested: freshly prepared, mechanically sheared, freeze-thawed, freeze-dried, and hydrolyzed mucus. The results demonstrate that jellyfish mucus can efficiently sequester polystyrene microplastics particles from the suspension. The fraction of the removed microplastics was highest with freshly prepared mucus and decreased with freeze-thawing and freeze-drying. The mucus ability to sequester microplastics was completely lost in the hydrolyzed mucus. The results imply that the intact jellyfish mucus has the potential to be used as a biopolymer capable of removing microplastics material.

The Essentials of Marine Biotechnology - Ana Rotter; Michéle Barbier; Francesco Bertoni; Atle M. Bones; M. Leonor Cancela; Jens Carlsson; Maria F. Carvalho; Marta Cegłowska; Jerónimo Chirivella-Martorell; Meltem Conk Dalay; Mercedes Cueto; Thanos Dailianis; et al. (Frontiers in Marine Science, 2021)
Coastal countries have traditionally relied on the existing marine resources (e.g., fishing, food, transport, recreation, and tourism) as well as tried to support new economic endeavors (ocean energy, desalination for water supply, and seabed mining). Modern societies and lifestyle resulted in an increased demand for dietary diversity, better health and well-being, new biomedicines, natural cosmeceuticals, environmental conservation, and sustainable energy sources. These societal needs stimulated the interest of researchers on the diverse and underexplored marine environments as promising and sustainable sources of biomolecules and biomass, and they are addressed by the emerging field of marine (blue) biotechnology. Blue biotechnology provides opportunities for a wide range of initiatives of commercial interest for the pharmaceutical, biomedical, cosmetic, nutraceutical, food, feed, agricultural, and related industries. This article synthesizes the essence, opportunities, responsibilities, and challenges encountered in marine biotechnology and outlines the attainment and valorization of directly derived or bio-inspired products from marine organisms. First, the concept of bioeconomy is introduced. Then, the diversity of marine bioresources including an overview of the most prominent marine organisms and their potential for biotechnological uses are described. This is followed by introducing methodologies for exploration of these resources and the main use case scenarios in energy, food and feed, agronomy, bioremediation and climate change, cosmeceuticals, bio-inspired materials, healthcare, and well-being sectors. The key aspects in the fields of legislation and funding are provided, with the emphasis on the importance of communication and stakeholder engagement at all levels of biotechnology development. Finally, vital overarching concepts, such as the quadruple helix and Responsible Research and Innovation principle are highlighted as important to follow within the marine biotechnology field. The authors of this review are collaborating under the European Commission-funded Cooperation in Science and Technology (COST) Action Ocean4Biotech – European transdisciplinary networking platform for marine biotechnology and focus the study on the European state of affairs.

A New Network for the Advancement of Marine Biotechnology in Europe and Beyond - Ana Rotter; Ariola Bacu; Michèle Barbier; Francesco Bertoni; Atle M. Bones; M. Leonor Cancela; Jens Carlsson; Maria F. Carvalho; Marta Cegłowska; Meltem Conk Dalay; Thanos Dailianis; Irem Deniz; et al. (Frontiers in Marine Science, 2020)

Genetic associations with lipoprotein subfraction measures differ by ethnicity in the multi-ethnic study of atherosclerosis (MESA) - Zhe Wang; Ani Manichukal; David C. Goff; Samia Mora; Jose M. Ordovas; Nicholas M. Pajewski; Wendy S. Post; Jerome I. Rotter; Michele M. Sale; Stephanie A. Santorico; David Siscovick; Michael Y. Tsai; et al. (Human Genetics, 2017)

Genetic variants associated with VLDL, LDL and HDL particle size differ with race/ethnicity - Alexis C. Frazier-Wood; Ani Manichaikul; Stella Aslibekyan; Ingrid B. Borecki; David C. Goff; Paul N. Hopkins; Chao-Qiang Lai; Jose M. Ordovas; Wendy S. Post; Stephen S. Rich; Michèle M. Sale; David Siscovick; et al. (Human Genetics, 2013)

Velvet bentgrass (Agrostis canina L.) is the likely ancestral diploid maternal parent of allotetraploid creeping bentgrass (Agrostis stolonifera L.) - David Rotter; Karen V. Ambrose; Faith C. Belanger (Genetic Resources and Crop Evolution, 2010)

Analysis of EST sequences suggests recent origin of allotetraploid colonial and creeping bentgrasses - David Rotter; Arvind K. Bharti; Huaijun Michael Li; Chongyuan Luo; Stacy A. Bonos; Suleiman Bughrara; Geunhwa Jung; Joachim Messing; William A. Meyer; Stephen Rudd; Scott E. Warnke; Faith C. Belanger (Molecular Genetics and Genomics, 2007)

Evolution of Novel O-methyltransferases from the Vanilla planifolia Caffeic Acid O-methyltransferase - Huaijun Michael Li; David Rotter; Thomas G. Hartman; Fulya E. Pak; Daphna Havkin-Frenkel; Faith C. Belanger (Plant Molecular Biology, 2006)